Common-channel signalling - Manterfield, Richard J. (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1991)
A highly readable and lucid introduction to the complex subject of signalling enabling the reader to understand detailed signalling specifications and international standards recommendations.
Electronic reproduction.
Keywords: Telecommunication -- Switching systems; Signal processing -- Digital techniques; Electronic books